2016
DOI: 10.1097/lgt.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

An Insight Into Cervical Cancer Screening and Treatment Capacity in Sub Saharan Africa

Abstract: OBJECTIVE Approximately 85% of cervical cancer cases and deaths occur in resource-constrained countries where best practices for prevention, particularly for HIV-infected women, still need to be developed. The objective of this study was to assess cervical cancer prevention capacity in select HIV clinics located in resource-constrained countries. METHODS A cross-sectional survey of sub-Saharan African sites of four NIH-funded HIV/AIDS networks was conducted. Sites were surveyed on the availability of cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…The feasibility of expanding coverage to remote areas might be improved if screening can be integrated into existing HIV clinics that serve women with and without HIV infection. A recent survey of HIV networks in sub‐Saharan Africa indicated that on‐site access to cervical cancer screening with HPV testing was available at 18% of surveyed facilities, with cryotherapy available at 57% of sites . None of the HIV facilities that offer HPV testing in the survey were in Uganda, although some Ugandan clinics offer VIA and cryotherapy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of expanding coverage to remote areas might be improved if screening can be integrated into existing HIV clinics that serve women with and without HIV infection. A recent survey of HIV networks in sub‐Saharan Africa indicated that on‐site access to cervical cancer screening with HPV testing was available at 18% of surveyed facilities, with cryotherapy available at 57% of sites . None of the HIV facilities that offer HPV testing in the survey were in Uganda, although some Ugandan clinics offer VIA and cryotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of HIV networks in sub‐Saharan Africa indicated that on‐site access to cervical cancer screening with HPV testing was available at 18% of surveyed facilities, with cryotherapy available at 57% of sites . None of the HIV facilities that offer HPV testing in the survey were in Uganda, although some Ugandan clinics offer VIA and cryotherapy . Integration of HIV and cervical cancer screening programs has been identified as potentially beneficial by stakeholders in Uganda, if health worker shortages can be addressed .…”
Section: Discussionmentioning
confidence: 99%
“…However, use of dual Pap and VIA also has unique resource requirements and limitations, not too dissimilar to HR-HPV testing (e.g. specialized training and re-training for optimal performance, potential loss to follow-up awaiting the Pap result, and so on)[21]. Our results indicate that VIA alone, despite the benefit of a single visit approach in a population with high loss to follow-up, is not adequate for post-treatment screening since it would have missed nearly three-quarters of CIN2+ cases.…”
Section: Discussionmentioning
confidence: 99%
“…The latter would only be possible if the eggs are viable, whereas calcified eggs would not excrete DNA. With promotion of the Sustainable Development Goals, there will be greater attention placed on women's well-being, which in part will focus upon reducing cervical cancers and increased screening for human papilloma virus (HPV) (Coleman et al 2016). It is evident that where urinary schistosomiasis is coendemic the health system should integrate detection of FGS within such wider surveillance.…”
Section: Discussionmentioning
confidence: 99%